Cooperative Compliance no Brasil: análise do cenário nacional da conformidade cooperativa - Dantas, Glauber Isaias Pinheiro (2023)
The scope of this work is to analyze the relationship between the tax authorities and the taxpayer, addressing the relational and organizational history, as well as the impacts experienced so far, in order to verify what are the deficiencies that taint the model practiced by the tax administration and how the dialogic perspective can help to overcome these obstacles. After the analysis, the characteristics of the Cooperative Compliance model outlined by the OECD are highlighted, pointing out how this model relates to the constitutional objectives of tax administration. Then, the work analyzes the compliance initiatives in operation in the country, led by the União Federal and the states of Alagoas, Ceará, São Paulo and Rio Grande do Norte, and their actions to encourage taxpayer compliance and cooperate in the fulfillment of the main and ancillary obligations. It is a bibliographic research, using the deductive method, from the expansion of the discursive elaborations exposed by the authors presented, the panorama of the constitutional tax administration is outlined, confronting it with the proposed cooperative administrative model, highlighting the points of contrast with the constitutional objectives and with the project itself and characteristics proposed by the OECD.